Local impedance for the optimization of radiofrequency lesion delivery: A review of bench and clinical data. (25th December 2021) - Chu, Gavin S.; Calvert, Peter; Futyma, Piotr; Ding, Wern Yew; Snowdon, Richard; Gupta, Dhiraj
Abstract: Introduction: Radiofrequency catheter ablation is a cornerstone of treatment for many cardiac arrhythmias. Progression in three‐dimensional mapping and contact‐force sensing technologies have improved our capability to achieve success, but challenges still remain. Methods: In this article, we discuss the importance of overall circuit impedance in radiofrequency lesion formation. This is followed by a review of the literature regarding recently developed "local impedance" technology and its current and future potential applications and limitations, in the context of established surrogate markers currently used to infer effective ablation. Results: We discuss the role of local impedance in assessing myocardial substrate, as well as its role in clinical studies of ablation. We also discuss safety considerations, limitations and ongoing research. Conclusion: Local impedance is a novel tool which has the potential to tailor ablation in a manner distinct from other established metrics.